Tindak Tutur Lokusi dalam Daftar Putar "Belajar Filsafat" pada Channel Satu Persen - Indonesian Life School di kanal YouTube - Fathan Iqbal; Aulia Yasmin; Shinta Widiawati; Maulana Adi Saputra; Syifa Rindi Sapitri; Asep Purwo Yudi Utomo; Arum Yuliya Lestari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Communication in digital media, especially YouTube, now plays an important role as a means of delivering educational material to the wider community. Nevertheless, studies on the phenomenon of communication on this platform, especially from the perspective of locutionary acts, are still limited. Philosophy-themed content, which is often considered abstract and complex, requires linguistic analysis to understand effective communication patterns. This study aims to identify and describe various forms of locutionary acts that appear in the “Belajar Filsafat” (Learning Philosophy) playlist on the YouTube channel Satu Persen – Indonesian Life School. This study was conducted using a qualitative descriptive method based on pragmatic theory. Data were collected through observation and note-taking techniques in four videos from the playlist, then analyzed using matching techniques and presented informally. The results of the study show that there are 151 locutionary acts, including 76 declarative acts, 46 interrogative acts, and 29 imperative acts. Theoretically, this study contributes to the development of linguistic studies, particularly in the field of pragmatics that discusses speech acts, while practically, this study can be a reference for students and novice researchers in understanding speech act research methods and the importance of applying effective communication in the realm of digital education.